INFLUENCE OF FERTILIZER APPLICATION RATIO ON FIELD CROP ROTATION EFFECTIVENESS - Н. Нospodarenko (Наукові горизонти, 2019)
The article presents the results of study the influence of various doses and ratios of mineral fertilizers on the yield of field crop rotation and calculates its effectiveness for two rotations on podzolized heavy clay loam chernozem within the conditions of the right-bank forest-steppe of Ukraine. The research was conducted under the conditions of a stationary field experiment established in 2011, the main point of which is to study the possibility of reducing the dose of mineral fertilizers in field crop rotation. On the basis of conducted researches, it was found that on average for two field crop rotations, different systems of fertilizers application contribute to increase in productivity of crop rotation by 41–107%. It should be noted that the exclusion from the composition of complete mineral fertilizer (N110P60K80) of the nitrogen component reduced it by 36%, phosphorous – by 17 and potassium - by 12% only. The application of half of this fertilizer dose (variant N55P30K40) reduced productivity of crop rotation by 21%. The least average annual decrease in productivity of crop rotation - by 0.30–0.51 t of grain units/ha or only 4-6% was noted in the experimental versions of N110P60K40 and N110P30K80, whereas in variant N110P30K40 it was more significant - 0.67 t of grain units/ ha or by 9%. Crops of crop rotation had a different influence on its productivity according to the main products. By this indicator they can be placed in the following series: corn> winter wheat> spring barley> soybeans. It accordingly changed their influence on the formation of crop rotation productivity. Mostly, the formation of organic carbon in the field crop rotation is affected by nitrogen fertilizers. At crop rotation saturation of mineral fertilizers at a dose of N55P30K40 per 1 kg of their active ingredient account for 2.37 kg of organic carbon, or 37% more compared to N110P60K80 dose. This is less than preferred amount. However, it should be noted that, along with organic carbon of the non-market part of the crop yield, the stubble and plant roots remain in the soil, which were not taken into account.